A highly stretchable and sensitive strain sensor based on graphene–elastomer composites with a novel double-interconnected network. Issue 26 (16th June 2016) - Lin, Yong; Liu, Shuqi; Chen, Song; Wei, Yong; Dong, Xuchu; Liu, Lan
Abstract : A facile assembly approach was firstly reported to fabricate a highly stretchable and sensitive strain sensor based on graphene–rubber composites with a novel double-interconnected network. Abstract : The construction of a continuous conductive network with a low percolation threshold plays a key role in fabricating a high performance strain sensor. Herein, a highly stretchable and sensitive strain sensor based on binary rubber blend/graphene was fabricated by a simple and effective assembly approach. A novel double-interconnected network composed of compactly continuous graphene conductive networks was designed and constructed using the composites, thereby resulting in an ultralow percolation threshold of 0.3 vol%, approximately 12-fold lower than that of the conventional graphene-based composites with a homogeneously dispersed morphology (4.0 vol%). Near the percolation threshold, the sensors could be stretched in excess of 100% applied strain, and exhibited a high stretchability, sensitivity (gauge factor ∼82.5) and good reproducibility (∼300 cycles) of up to 100% strain under cyclic tensile tests. The proposed strategy provides a novel effective approach for constructing a double-interconnected conductive network using polymer composites, and is very competitive for developing and designing high performance strain sensors.